Thalidomide Analogs in Brazil: Concern About Teratogenesis - Fernanda Sales Luiz Vianna; Maria Teresa Vieira Sanseverino; Lavinia SchÃ¼ler Faccini (Fundação Oswaldo Cruz (FIOCRUZ), 2014)
It has been more than 50 years since thalidomide was withdrawn from the world market due to its teratogenic potential. However, its widespread use around the world resumed due to its immunomo-dulatory and anti-angiogenic properties. The drug established itself in new therapies, and interest continued with the emergence of more potent analogs, the most notable being lenalidomide and pomalidomide, which are not approved in Brazil. The question that arises after analog synthesis is: Do these drugs also have the same teratogenic potential? The answer to this question is based only on experimental studies because exposure to humans is not authorized and has not yet been descri-bed. Although thalidomide has been recognized as a powerful human teratogen for many years, its molecular mechanisms of teratogenesis remain to be fully explained. Efforts with animal models and human genetic studies have clarified some important pathways that are most likely involved in the teratogenic action of thalidomide. However, it has not yet been possible to identify the teratogenic domain of the molecule from the therapeutic ones. Moreover, there are species-specific differences that must be taken into consideration when teratogenicity is evaluated.